Drug-Drug interactions with direct oral anticoagulants - Foerster, Kathrin; Hermann, Simon; Mikus, Gerd; Haefeli, Walter E. (Clinical pharmacokinetics, 2020)
A large body of evidence suggests that not only direct anticoagulant effects but also major bleeding events and stroke prevention depend on plasma concentrations of direct oral anticoagulants (DOACs). Concomitant drugs that cause drug-drug interactions (DDIs) alter DOAC exposure by increasing or decreasing DOAC bioavailability and/or clearance; hence, they might affect the efficacy and safety of DOAC therapy. Patients with renal impairment already receive smaller DOAC maintenance doses because avoidance of elevated DOAC exposure might prevent serious bleeding events. For other causes of increased exposure such as DDIs, management is often less well-defined. Considering that DOAC patients are often older and have multiple co-morbidities, polypharmacy is highly prevalent. However, the effect of multiple drugs on DOAC exposure, and especially the impact of DDIs when concurring with drug-disease interactions as observed in renal impairment, has not been thoroughly elucidated. In order to provide effective and safe anticoagulation with DOACs, understanding the mechanisms and magnitude of DDIs appears relevant. Instead of avoiding drug combinations with DOACs, more DDI trials should be conducted and new strategies such as dose adjustments based on therapeutic drug monitoring should be investigated. However, dose adjustments based on concentration measurements cannot currently be recommended because evidence-based data are missing.
Gesehen am 14.09.2020